Financial statement analysis was conducted to assess the financial performance of PT Unilever Indonesia Tbk in the 2018-2022 period using the Current Ratio, Debt Equity Ratio, and Return on Asset - Ina, Ina; Octavia, Afini Dhea; Fauziah, Tika; Haryadi, Didit (International Journal of Applied Finance and Business Studies, 2024)
Financial performance is a formal effort to evaluate the efficiency and effectiveness ofa company in generating profits. The method used is a qualitative method using a descriptive approach; the subject in this study is PT Unilever Indonesia Tbk and the object in this study is the financial statement data of PT Unilever Indonesia Tbk. The data source used in this study is secondary data taken from the official website of PT Unilever Indonesia Tbk. This study aims to determinethe financial performance of PT Unilever Indonesia Tbk using the CurrentRatio, debt-to-equityRatio, and return on assets. It is expected to provide helpful information for companies and investors in making investment decisions. Based on the attached data, it shows that during the 2018-2022 period, the average Ratio of each Ratio in PT Unilever Indonesia Tbk is as follows: at the liquidity ratio of current assets of 8,178,740 and current liabilities of 12,488,997. At the Ratio of total debt solvency of 14,415,546 and total equity of 5,223,178. Theprofitability ratio of total assets amounted to 56,794,724, and net profit amounted to 6,955,753. From the results of this study, the Company's financial performance shows a low level of liquidity, a higher level of risk due to the use of more considerable debt, and suboptimal operational performance. Therefore, companies must pay attention to cost management, debt management, and sales activities to improve financial performance. TheCompanyCompany should increase sales toenhance efficient financial performance. This research is expected to make theoretical contributions to the literature in this context, including in the context of economic and banking management.